Theoretical study of spin-orbit coupling and laser cooling for HBr molecule with first-overtone spectral calculations - Yassine, Khadija; El-Kork, Nayla; Abu El Kher, Nariman; Younes, Ghassan; Korek, Mahmoud (Frontiers in Physics, 2025)
IntroductionThe electronic structure of the HBr molecule was investigated with particular attention to the spin–orbit coupling effect, aiming to assess its suitability for laser cooling applications.MethodsAb initio CASSCF/MRCI+Q calculations were carried out to obtain low-lying adiabatic potential energy curves with and without spin–orbit coupling taken into consideration. Static and transition dipole moments were evaluated, and the DUO and ExoCross programs were employed to simulate rovibronic spectra. Franck–Condon factors were calculated for transitions between the ground and excited electronic states.ResultsThe spectroscopic constants of several electronic states were derived and compared with available literature values, showing good agreement. The Franck–Condon factor analysis identified a transition as favorable for Doppler and Sisyphus laser cooling. Radiative lifetimes, branching ratios, Doppler and recoil temperatures, and slowing distances were determined. A four-laser cooling scheme in the deep-UV region was proposed. Simulated absorption spectra for the P(2) and R(7) transitions in the first-overtone (v = 0–2) band reproduced experimental data with reasonable accuracy.DiscussionThese findings confirm HBr as a promising candidate for laser cooling, supported by reasonably accurate ab initio potential and dipole moment curves. The proposed scheme and agreement with experimental spectra strengthen the feasibility of experimental implementation.